Modifiable Risk Factors Linked to Late Stages of Chronic Kidney Disease in Saudi Arabia: Life Sciences -Medicine - Abdullah Alshammari, Hessa; Khalid Alquwaiay, Fahad; Fahad Aldhamadi, Hamoud; Ali Alqufayi, Abdulkarim; A. Alrashidi, Ahmed; Alzayed, Faisal Saud Mohammed; Ali Alshammari, Omar; Ahmed Alogla, Saleh; Gadelkarim Ahmed, Hussain (International Journal of Life Science and Pharma Research, 2023)
The present study aims to identify modifiable risk variables associated with late-stage chronic renal disease (CKD) in Saudi Arabia. During a cross-sectional survey in the Hail region, 256 Saudi participants were recruited for this study. Participants were chosen based on their estimated GFR. Only CKD patients in stages III, IV or V were eligible. Females had a higher prevalence of CKD, but male patients had a higher risk of end-stage disease, with an RR (95% CI) of 3.2893 (1.4416 to 7.5055), P = 0.0047. Hypertension was found in 62% of the participants (43% in Stage IV and 45.5% in Stage V). T2DM was found in 54% of the patients, with 60% having Stage IV and 27% having Stage V. Nonsteroidal anti-inflammatory medicines (NSAIDs) were used by 23% of the individuals (including 27% in Stage IV and 27% in Stage V). Herbal treatment was used by 21% of the patients (including 27% Stage IV and 36% Stage V). Late-stage CKD is prevalent in Saudi Arabia and is more common among women, rural residents, and people over 55. The findings of this study indicate that hypertension, diabetes, herbal medication use, nonsteroidal anti-inflammatory drugs (NSAIDs), and obesity are responsible for the increased prevalence of CKD in Saudi Arabia. Awareness and education programs focusing on modifiable risk factors for CKD are suggested for lowering the CKD prevalence rate.